Successive syntheses and magnetic properties of homodinuclear lanthanide macrocyclic complexes. Issue 35 (16th August 2021) - Li, Xiang; Liu, Yu-Han; Zhu, Guang-Zhou; Yang, Feng-Lei; Gao, Feng
Abstract : Two series of homodinuclear lanthanide macrocyclic complexes with D 4d symmetry have been successively synthesized. Magnetic studies reveal ferromagnetic interactions between Dy 3+ or Tb 3+ centres and typical SMM behaviors for Dy complexes 1 and 4 . Abstract : A series of homodinuclear β-diketone lanthanide(iii ) complexes, formulated as [(acac)4 Ln2 (L1)] (Ln 3+ = Dy 3+ (1 ), Tb 3+ (2 ), and Gd 3+ (3 ), respectively) were first synthesized based on a closed-macrocyclic ligand (H2 L1) derived from the [2 + 2] cyclocondensation of 4- tert -butyl-2, 6-diformylphenol and o -phenylenediamine in the presence of lanthanide acetylacetonates. Subsequently, by using the above compounds as building blocks to assemble directly with another Schiff base ligand, N, N ′-bis(5-chlorosalicylidene)- o -phenylenediamine (H2 L2), three new homodinuclear sandwich-type lanthanide complexes with the general formula [Ln2 (L1)(L2)2 ] (Ln 3+ = Dy 3+ (4 ), Tb 3+ (5 ), and Gd 3+ (6 ), respectively) were further designed and prepared. Single-crystal X-ray analyses show that the central Ln 3+ ion adopts a distorted square antiprism conformation with D 4d local symmetry. Magnetic studies reveal ferromagnetic interaction between Dy 3+ and Tb 3+ centres and zero-field slow relaxation of magnetization for Dy complexes 1 and 4 . The corresponding magneto-structural correlations of SMMs 1 and 4 were further discussed by theoretical calculations and with experimental outcomes.